Livestock development in Nigeria, 1914-1979: A brief historical review - Walker, D.A.W. (International Livestock Centre for Africa, 1981)
A brief account of the history of the development of livestock production in Nigeria, which is closely related to the development of veterinary services, emphasizing the significance of rinderpest in this development. Discusses the part played by dif. institutions and governmental bodies, w. note on staffing and financing of veterinary services and training within the country.